2006
DOI: 10.1161/01.atv.0000236200.02726.f7
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution X-Ray Microtomography Is a Sensitive Method to Detect Vascular Calcification in Living Rats With Chronic Renal Failure

Abstract: Objective-Chronic renal failure (CRF) is associated with a 10-to 20-fold increase in cardiovascular risk. Vascular calcification is a prominent feature of cardiovascular disease in patients with end-stage renal failure and contributes to the excess mortality in this population. In this study, we explored in vivo X-ray microtomography (micro-CT) as a tool to detect and follow-up vascular calcifications in the aorta of living rats with adenine-induced CRF. Methods and Results-With in vivo micro-CT, calcification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 23 publications
0
30
0
Order By: Relevance
“…Previous studies 21,22 in our laboratory demonstrated that the induction of CRF with an adenine-rich diet containing a normal protein content results in calcification of the aortic tunica media in approximately 50% of the animals after 4 to 6 weeks. However, lowering the protein content from 19% to 2.5% during the 4-week adenine treatment period resulted in a remarkably increased prevalence of severe medial calcifications up to 100% in rats with CRF.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Previous studies 21,22 in our laboratory demonstrated that the induction of CRF with an adenine-rich diet containing a normal protein content results in calcification of the aortic tunica media in approximately 50% of the animals after 4 to 6 weeks. However, lowering the protein content from 19% to 2.5% during the 4-week adenine treatment period resulted in a remarkably increased prevalence of severe medial calcifications up to 100% in rats with CRF.…”
Section: Discussionmentioning
confidence: 82%
“…21 Therefore, a separate group of rats with CRF (nϭ10) was scanned at 1, 2, 3, 4, 6, and 8 weeks after the induction of CRF.…”
Section: In Vivo Micro-computed Tomographymentioning
confidence: 99%
“…With regard to future studies aiming to investigate the reversal of vascular calcification, in vivo microtomography scanning has been shown to be a sensitive tool for the follow-up of aortic calcification in living rats. 149 …”
Section: Resultsmentioning
confidence: 99%
“…The degree of von Kossa positivity was scored semiquantitatively, with scores ranging from 0 to 3 depending on the surface of von Kossa positivity. Score 0 indicated no von Kossa positivity; score 1, focal von Kossa positivity, larger than or not overlying a cell nucleus; score 2, partially circumferential von Kossa positivity in the tunica media of the vessel; and score 3, von Kossa positivity in the tunica media spanning the complete circumference of the vessel (Persy et al, 2006a;Neven et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…The aortic rings visible on a 40Â magnification were captured on a microcomputer equipped with Leica software (Leica Microsystems, Buffalo Grove, IL) and analyzed by a computerized image analysis program. Semiquantitative assessments of nitrotyrosine and CD68 expressions were done by semiautomatic quantification of brown-field expression specifically inside aorta media, as described previously Persy et al, 2006a). Data were expressed as the relative proportion (percentage) of the positive staining area of the aorta media to total surface area of each ring.…”
Section: Methodsmentioning
confidence: 99%